A tranferência do risco no contrato de venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena de 1980 - Damião, Ana Raquel Modesto (Universidade Nova de Lisboa, 2017)
International trade has had an increasing impact on the national economies of states. For this reason, some international institutions have sought to standardise rules on the international sale of goods. The Convention, which stands out from these rules, is the United Nations Convention on Contracts for the International Sale of Goods, opened for signature in Vienna on 11th April, 1980, known as the Vienna Convention (CISG). The transfer of risk is one of the most sensitive issues in international trade. Therefore, it would seem apt to observe the legal regime of the transfer of risk contained in the various provisions of this international instrument. To understand the rules of the transfer of risk, it is necessary to observe the notion of contract for the international sale and the obligations of the parties involved in the international contract. In addition, it should be noted that, in most situations, the contract for the international sale is related to the transport of goods. With this framework, the study of this essay focuses on the analysis of article 68 of the Vienna Convention. So, this dissertation deals with the question of determining the exact moment of the transfer of risk in the contract of international sale of goods in transit under the Vienna Convention. O comércio internacional tem tido cada vez mais impacto nas economias nacionais dos Estados. Por esse motivo, algumas organizações internacionais têm procurado uniformizar as regras relativas à compra e venda internacional de mercadorias. A Convenção, que se destaca dessas regras, é a Convenção das Nações Unidas sobre os Contratos de Compra e Venda Internacional de Mercadorias, aberta à assinatura em Viena a 11 de abril de 1980, conhecida como Convenção de Viena. A transferência do risco apresenta-se como uma das temáticas mais delicadas do comércio internacional. Portanto, afigura-se como útil a observação do regime jurídico da transferência do risco contido nas diversas disposições deste instrumento internacional. Para compreender as regras da transferência do risco, é necessário observar a noção de contrato de compra e venda internacional e as obrigações das partes do contrato internacional. Além disso, há que perceber que, na generalidade das situações, o contrato de compra e venda internacional está relacionado com o transporte de mercadorias. Com este enquadramento, o estudo deste trabalho centra-se na análise do artigo 68.º da Convenção de Viena. Assim, a presente dissertação debruça-se sobre a questão de determinar qual é o momento exato da transferência do risco no contrato de compra e venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena.
Keywords: Convenção de Viena; Goods in transit; International sale; Mercadorias em trânsito; Transfer of risk; Transferência do risco; Venda internacional; Vienna Convention

The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
URI: https://www.tdx.cat/handle/10803/404845
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

A Pluralist Approach to the Law of International Sales - Coetzee, Juana (Potchefstroom Electronic Law Journal, 2017)
International trade can support economic development and social upliftment. However, people are often discouraged from contracting internationally due to differences in legal systems which act as a non-tariff barrier to trade. This article focuses on the private law framework regulating international contracts of sale. During the twentieth century, the problem of diverse laws was primarily addressed by global uniform law such as the United Nations Convention on Contracts for the International Sale of Goods (CISG). However, uniform law is rarely complete and has to be supplemented by national law, trade usage or party agreement. Because of gaps that exist in the CISG the Swiss government made a proposal for a new global contract law. But is this a feasible solution to the fragmentary state of international trade law? In Europe, signs of reluctance are setting in towards further harmonisation efforts. The Proposal for a Common European Sales Law (CESL) was recently withdrawn, and now Britain has voted to leave the European Union; rumour having it that more countries might follow. The current private law framework for international sales contracts consists of a hybrid system where international, national, state and non-state law function side by side. This article submits that universalism is not per se the most efficient approach to the regulation of international sales law and that economic forces require a more varied approach for business-to-business transactions. The biggest challenge, however, would be to manage global legal pluralism. It is concluded that contractual parties, the courts and arbitral tribunals can effectively manage pluralism on a case-by-case basis.
Keywords: Global legal pluralism; Legal harmonisation; international contracts; international sales; unified law

Previsibilidade do dano contratual como critério limitador de responsabilidade no Direito do Comércio Internacional - Barros, Vera Cecilia Monteiro de (Universidade de São Paulo, 2017)
O objetivo central desta tese é avaliar se a regra da previsibilidade do dano contratual ressarcível é um método eficaz de limitação dos danos e se atende às exigências modernas do Comércio Internacional. Para o perfeito enquadramento e contextualização do tema central deste estudo, apresenta-se inicialmente a origem histórica do critério da previsibilidade do dano no campo da responsabilidade contratual, e faz-se uma análise do alcance do princípio da reparação integral do dano e do princípio geral de ressarcimento de dano no Direito romano. Em seguida, realiza-se um breve exame do Direito Contratual na França até o século XVI, bem como uma análise do ressarcimento do dano nas obras de Dumoulin, Domat e Pothier e, para encerrar a parte histórica, analisa-se o Código Civil francês e a obrigação de ressarcimento. Ato contínuo, adentra-se a fundo nas noções gerais e nuances da regra da previsibilidade do dano, verificando-se, inicialmente, o sentido geral da limitação. Em seguida, analisa-se a teoria do fim tutelado pelo contrato e os fundamentos (contratual e econômico) do critério da previsibilidade. Feito isso, são avaliados o objeto e o momento da previsibilidade e, após, a (não) limitação de responsabilidade ao devedor doloso. Na sequência, estuda-se a adoção da previsibilidade do dano contratual como critério limitador do ressarcimento nos sistemas domésticos e em alguns dos principais instrumentos internacionais de uniformização do direito europeu, quais sejam, nos Princípios de Direito Europeu dos Contratos (PECL), no Draft Common Frame of Reference (DCFR), no Common European Sales Law (CESL) e no Projeto do Código Europeu dos Contratos. Em seguida analisa-se dois dos principais instrumentos de harmonização normativa do Comércio Internacional: os princípios do International Institute for the Unification of Private Law (Unidroit) e, mais profundamente, a Convenção das Nações Unidas sobre Contratos de Compra e Venda Internacional de Mercadorias (CISG), que hoje é referência normativa para os contratos internacionais entre signatários, os quais representam dois terços do comércio mundial. E, por fim, faz-se a análise econômica da regra da previsibilidade com o objetivo, primeiramente, de se verificar se, de fato, ela promove eficiência econômica e se a sua previsão influencia o comportamento das partes, incentivando a revelação de informações relevantes. E, na medida em que a previsibilidade do dano é um conceito jurídico indeterminado, cujo desafio da doutrina e especialmente da jurisprudência é dar a ele contornos mais concretos e objetivos, analisase decisões judiciais e arbitrais que aplicaram e interpretaram a regra da previsibilidade do dano no âmbito da CISG para, depois, avaliar, também mediante a análise econômica do Direito, a forma como o posicionamento de juízes e árbitros sobre a referida regra afeta os custos de transação dos negócios comerciais internacionais. The main purpose of the thesis herein is to evaluate if the foreseeability rule regarding refundable contractual damage is an effective method of damages limitation and whether it attends the modern International Trade requirements. For the perfect framing and contextualization of the central theme of this study, it is initially presented the historical origin of the damage foreseeability criteria in the field of contractual liability and an analysis is made of the scope of the principle of full compensation for damage and of the general principle of compensation in Roman Law. Then, a brief examination of the Contract Law in France until the sixteenth century is carried out, as well as an analysis of reparation of damages in the works of Dumoulin, Domat and Pothier and, to close the historical part, the French Civil Code and the obligation to make reparation are also analyzed. Subsequently, it goes deeper into the general notions and nuances of the foreseeability damage rule, initially finding the general meaning of the limitation. Next, we analyze the theory of the purpose protected by the contract and the fundamentals (contractual and economic) of the criteria of foreseeability. Later, the object and the moment of foreseeability are evaluated, as well as the (non) limitation of liability to the intentional debtor. Following, it is herein studied the adoption of foreseeability of contractual damage as a limiting criterion for reimbursement in domestic systems and in some of the main international instruments for the standardization of European law, namely in the European Contract Law Principles (ECLP), in the Draft Common Frame of Reference (DCFR), in Common European Sales Law (CESL) and in the Draft of the European Code of Contracts. Two main instruments of normative harmonization of international trade are discussed below: the principles of the International Institute for the Unification of Private Law (Unidroit) and, more profoundly, the United Nations Convention on Contracts for the International Sale of Goods (CISG), which is currently the normative reference for international contracts among signatories, which represent twothirds of world trade. Finally, the economic analysis of the foreseeability rule is carried out, initially, in order to verify whether it promotes economic efficiency and whether its prediction influences the behavior of the parties, encouraging the disclosure of relevant information. And insofar as the damage foreseeability is an indeterminate legal concept, whose challenge in the doctrine and especially the jurisprudence is to give it more concrete and objective outlines, we analyze judicial and arbitral decisions that applied and interpreted the rule of foreseeability within the scope of the CISG, in order to afterwards assess, also upon the economic analysis of the Law, how the position of judges and arbitrators on such rule affects the transaction costs of international business.
Keywords: CISG; Commerce international; Comércio internacional; Contract damage; Dano contratual; Direito Comercial Internacional; Foreseeability; International Trade; Liability; Limitation; Reparação do dano; Responsabilidade contratual

طرق تحديد القانون الواجب التطبيق على عقود التجارة الدولية - عيد, عبد الحفيظ (جامعة مولود معمري, 2017)
تظهر طرق تحديد القانون واجب التطبيق على عقود التجارة الدولية في كل من المنهج التنازعي الذي يقوم على قاعدة إسناد و المنهج المباشر الذي يقدم الحل للنزاع بطريقة مباشرة وذلك بتطبيق قواعد قانونية تهتم بتنظيم العلاقات التجارية ذات البعد الدولي والتي تعرف بقواعد التجارة الدولية . يعتبر المنهج التنازعي من أقدم مناهج التي عرفتها نظرية التنازع والتي عرفت تطورات تعكس الفكر الفلسفي والاقتصادي والقانوني الذي يتخلل كل مرحلة من هذا التطور إلى أن إستقر في الأخير مبدأ سلطان الإرادة على ضوؤه يتم تحديد قانون العقد الدولي . مع تطورات الحاصلة في التجارة الدولية خاصة بعد التطور العلمي والتكنلوجي وتطور وسائل النقل وظهور مجتمع خاص يمارس هذه التجارة، ظهرت الحاجة إلى تطبيق قواعد قانونية ذات مضمون عالمي تستوعب تعقيدات هذه العقود التي تجاوزت المفاهيم الكلاسيكية التي جاءت بها القوانين الداخلية التي صدرت لتنظيم العقود الداخلية . Les modes de détermination de la loi applicable aux contrats de commerce international Les modes de choix de la loi applicable sur les contrats de commerce international se dégagent à la fois de l’application de la méthode dite conflictuelle qui se base sur la règle du rattachement, et de la méthode dite directe qui propose une solution directe au litige et ce, en application des règles régissant les relations à caractère international. La méthode dite conflictuelle est la plus ancienne ; elle a connu plusieurs étapes dans son évolution qui ont caractérisées la pensée philosophique, économique et juridique, jusqu’à l’émergence du principe de l’autonomie de la volonté sur lequel se base le choix de la loi applicable sur le contrat international. L’évolution connue dans le commerce international notamment au plan scientifique et technologique, l’évolution des moyens de transport et l’apparition d’une société qui pratique ce commerce, a fait apparaitre le besoin de règles à vocation mondiale prenant en compte la complexité de ce type de contrats qui dépassent largement les concepts classiques liés aux contrats internes.
Keywords: Arbitrage commercial international; Contrats commerciaux internationaux; Loi applicable; Pouvoir de volonté; Règles d'attribution; التحكيم التجاري الدولي; القانون الواجب التطبيق; سلطان الإرادة; عقود التجارة الدولية; قواعد الإسناد

L'encadrement juridique de "Documents Transférables Électroniques" - Gamal Eldine, Nabil (Université de Montpellier, 2017)
L’intérêt de la présente recherche est d'étudier d’une manière générale les communications électroniques dans le commerce international, et puis à titre particulier d’interpeler les nouveaux défis qui relèveraient de l’utilisation des "documents transférables électroniques", en réfléchissant sur les différentes approches et les méthodes à adopter afin de remédier aux éventuelles déficiences technologiques, identifier puis combler les lacunes juridiques qui se révéler lors de ces échanges. Il s’agirait donc d’une enquête sur les questions juridiques liées à la création, à l’utilisation et à l’exécution du "document transférable électronique" ; il s’agit d’un terme crée par la CNUDCI, ce qui renvoie d’une manière générale à l’équivalent électronique d’un instrument transférable négociable ou d’un document titre. Nous identifions principalement les trois grands axes. Premièrement, la protection des données personnelles. Elle fait l’objet de plusieurs réformes législatives. La plus récente est le Règlement européen 2016/679 du 27 avril 2016 qui vise à promouvoir l’utilisation de l’outil informatique, tout en accordant la protection appropriée aux données à caractère personnel. Deuxièmement, l'exigence d’unicité d’un document transférable (« Garantie de singularité »). La garantie de l’unicité d’un document exige qu’il soit le seul qui existe ou bien, que toute copie soit clairement identifiable comme telle. Les conséquences éventuelles de la reproduction non autorisée de tout document transférable électronique donnant au porteur ou au bénéficiaire le droit de demander la remise de marchandises ou le paiement d’une somme d’argent rendent nécessaire l’élaboration de mécanismes pour garantir l’unicité de ces instruments. Troisièmement, la possession du ‘document transférable électronique’ et la notion de contrôle pour l’identification du porteur. Outre le traitement de la question de l’exigence de la singularité, la recherche d’un mécanisme fonctionnellement applicable et équivalent pour satisfaire à l’exigence de la possession matérielle du document papier constitue un défi majeur. Dans la plupart des modèles juridiques régissant les documents transférables électroniquement, la notion de “contrôle” d’un document électronique est utilisée en tant qu’équivalent fonctionnel de la possession ; cela signifie que la personne qui exerce le contrôle du document transférable électronique est considérée comme le porteur habilité à s’en prévaloir. Ces documents électroniques sont gérés par des prestataires de confiance qualifiés pour garantir leur sécurité. The interest of this research is to study in general, the electronic communications in an international context, and then to focus on the ongoing challenges that occur on the field of ''electronic transferable documents''; for this we shall perceive the methods that have been adopted for the purpose of using such documents, in order to prevent eventual technological deficiencies, identifying and filling the legal gaps revealed throughout our study of these new challenges.Therefore we shall comprehend and defy the legal boundaries, in order to create, use and transfer ''electronic transferable documents''. It is a pre-requisite to clearly identify the subject of this study, which is the term 'electronic transferable record, a concept created by UNCITRAL, which refers generally to ' Electronic equivalent of a transferable record (negotiable or non-negotiable) or a document of a legal right.We shall identify the three following main topics:I. The protection of personal data and privacy has been subject to several legislative reforms. The most recent one is the European Regulation 2016/679 dated April 27th, 2016. This reform aims to promote the use of the IT (Information Technology) tools, while granting the appropriate protection to the personal data. These electronic records are managed by qualified services providers.II. Requirement for uniqueness of the record (''Guarantee of uniqueness'')The guarantee of the uniqueness of the document is to ensure that there is only one possible holder and owner of that document, as in the case of paper document, and that any copy is clearly identifiable as such. As a result of an unauthorized reproduction of any electronic transferable record, any such holder or beneficiary shall have the right to request delivery of goods or the payment of a certain sum of money; thus the need to insure the uniqueness of these electronic records.III. The possession of an electronic transferable record.In addition to the above, the need to identify a functional equivalent approach to satisfy the requirement of possession in the case of electronic transferable document, which is a major challenge.IV. Concept of control and identification of the holderIn most legal models governing electronic transferable records, the definition of ''control'' of an electronic document is used as a functional equivalent to possession. That is, the person who controls the electronic transferable record is deemed to be the holder and the one entitled to use it.
Keywords: Bill of Exchange; Billet à ordre; Commerce électronique; Document transférable électronique; E-Commerce; Electronic signature; Gestion électronique de documents; Lettre de change; Promissory note; Signature électronique; Transferable records

Viyana satım sözleşmesi uyarınca teslim borcu - Davarci, Atakan Âdem (İstanbul Ticaret Üniversitesi, 2017)
CISG, yeknesak satım hukuku oluşturma çabasının bir sonucu olarak karşımıza çıkmaktadır. CISG'in temelini satım sözleşmesi oluşturur. Satım sözleşmesi insanların mal alımını sağlayarak ihtiyaçlarını karşılamasını sağlayan bir sözleşmedir. Satım hukukunun temelini satım sözleşmesi oluşturmaktadır. Satım sözleşmeleri tarafların mal ve satım bedeli üzerinde anlaşmaları ile kurulur. Satım sözleşmesinde satıcının asıl borcu ise sözleşmeye konu malın teslimidir. Malın doğru yer ve zamanda teslim edilmesi ve teslim edilen malın sözleşmeye uygun olması konuları teslimin en önemli unsurlarıdır. Malın sözleşmeye uygun olmaması veya sözleşmeye uygun yer ve zamanda teslim edilmemesi satıcının sözleşmeye aykırı davrandığını gösterir. Sözleşmeye aykırılığın tespiti, aykırılığın derecesine göre alıcıya bazı haklar tanımaktadır. Bu çalışma, hem teslim borcunun içeriğini hem de teslim borcu açısından sözleşmeye aykırılığı ayrıntılı olarak ele almaktadır. CISG emerges as a result of the effort to create a uniform selling law. The basis of the CISG is the contract of sale. The sale contract is a contract that allows people to buy goods and meet their needs. The sales contract constitutes the foundation of the law of sale. Sale contracts are established with the parties agreeing on the goods and sales price. The actual debt of the seller on the sales contract is the delivery of the goods subject to the contract. The fact that delivery at the right place and time and the delivered goods conform to the contract are the most important elements of delivery. The fact that the merchandise is incompatible with the contract or not delivered at the proper time and place indicates that the seller is breaching the contract. The determination of breach of contract gives the buyer some rights according to the degree of breach. This study elaborates on the contradiction to the contract in terms of both the content of the delivery debt and the delivery debt.
Tez N°478791
Keywords: CISG; Commercial law; Contracts; Milletlerarası Mal Satımlarına İlişkin Birleşmiş Milletler Antlaşması; Obligation to delivery; Sözleşmeler; Teslim borcu; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku; Vienna Sales Convention; Viyana Satım Sözleşmesi

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.